1984
DOI: 10.1007/bf00501436
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of three inotropic agents, ASL-7022, dobutamine and dopamine, with α- and β-adrenoceptors in vitro

Abstract: Three inotropic agents, ASL-7022, dobutamine and dopamine, were evaluated for their alpha- and beta-adrenoceptor mediated effects in vitro in a variety of isolated organs and in radioligand binding studies. All compounds were alpha 1-adrenoceptor agonists in rat and guinea pig aortae, but the rank orders of potency were exactly opposite in these two tissues. Only the rank potency order of dobutamine greater than ASL-7022 greater than dopamine obtained in rat aorta was consistent with the results obtained in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…One limitation of our experimental design is the limited selectivity of terbutaline and dobutamine at b 2 -and b 1 -adrenoceptors, respectively (Ruffolo et al, 1984;Young et al, 2002;Baker, 2005). This prevents us from using higher nonselective concentrations of those agonists because the mouse aorta relaxes to activation of both subtypes of b-adrenoceptors.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of our experimental design is the limited selectivity of terbutaline and dobutamine at b 2 -and b 1 -adrenoceptors, respectively (Ruffolo et al, 1984;Young et al, 2002;Baker, 2005). This prevents us from using higher nonselective concentrations of those agonists because the mouse aorta relaxes to activation of both subtypes of b-adrenoceptors.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we tested the potencies with which selective agonists for the β‐AR subtypes relaxed the human detrusor muscle. Neither dobutamine, which stimulates both β 1 ‐ and β 2 ‐ARs ( Ozaki et al ., 1982 ; Ruffolo et al ., 1984 ; Ruffolo, 1987 ; Aikawa et al ., 1996 ), nor procaterol, a β 2 ‐AR agonist, produced any significant relaxation at up to 10 −5 M . In fact, the concentration at which dobutamine and procaterol did induce a relaxing effect in our preparation was around 10 −4 M .…”
Section: Discussionmentioning
confidence: 99%
“…However, they found that the β 1 ‐agonist, dobutamine, was a poor relaxant of rat bladder smooth muscle. Although dobutamine is generally considered to be a β 1 ‐selective agonist, some studies have shown that it also has β 2 ‐agonist and α 1 ‐partial agonist actions ( Ozaki et al ., 1982 ; Ruffolo et al ., 1984 ; Aikawa et al ., 1996 ). In preliminary studies, we found that dobutamine caused a significant relaxation of KCl‐precontracted rat bladder strips with an EC 50 value of 6 μ M (data not shown), similar to that obtained with terbutaline.…”
Section: Discussionmentioning
confidence: 99%